(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
Pyrazinamide is a widely used drug for the treatment of tuberculosis. A 150 mg Dispersible Tablet (DT) formulation of the drug was prepared by Micro Labs, a generic drug company. The formulation was developed for easy administration into paediatric patients. It was tested for bioequivalence in healthy adult human volunteers in fasting condition. A total of 36 subjects were enrolled in the study and all the 36 subjects completed both the two periods of the study without showing major adverse events. The pharmacokinetic parameters determined for bioequivalence were Cmax and AUC0-t. The two parameters were within the limit of bioequivalence criteria. The 150 mg DT formulation developed by Micro Labs was found to be bioequivalent to 500 mg immediate release tablet formulation of Riemser Pharma. Both the formulations were safe and well tolerated among the tested human subjects. No major adverse events were observed.